Menelaah Pengertian, Macam, dan Tujuan Kisah- Kisah dalam Al-Quran - Shanera Arianti Nur Azizah; Annisa Mayyuris Naila; Rendi Samara Putra; Umar Al-Faruq (Pustaka Digital Indonesia, 2025)
The urgency of this research lies in the need for a deeper and more contextual understanding of the stories in the Qur’an, which have often been perceived merely as historical narratives or miracles. The stories within the Qur'an play a pivotal part in passing on lessons and ethical values to humankind. This investigate points to analyze the implications, assortments, and purposes of the stories contained within the Qur'an. The concept of stories within the Qur'an is caught on as a implies of conveying divine messages that are instructive and full of shrewdness. Different sorts of stories, such as those of the prophets, past countries, and illustrations, are explained to illustrate the differences and profundity of implications contained inside them. Moreover, this think about examines the purposes of these stories within the Qur'an, which incorporate instructive viewpoints, ingrains ethical values, reinforcing confidence, and giving lessons for humankind. With a comprehensive understanding of these stories, it is trusted that perusers can execute the values contained inside them into their every day lives, permitting the stories of the Qur'an to serve as important rules for living.